The Oxford handbook of Charles Brockden Brown - Barnard, Philip 1951-; Emmett, Hilary; Shapiro, Stephen 1964- (Oxford University Press, 2019)
"The Oxford Handbook of Charles Brockden Brown is a comprehensive and up-to-date collection on Brown's life and works. It includes original chapters on all of Brown's fictional and non-fictional writing and new considerations of his contexts, from the social, political, and economic to the scientific, commercial, and religious. The contributions speak in new ways about his depictions of literary theory, social justice, sexuality, and property relations, as well as slavery, Native Americans, and women's rights. His understanding of American and global history, of his own nation and foreign ones, and of selfhood and otherness, like all the other topics, is explained in terms easy to comprehend and profoundly relevant to emerging modernity" ...